SEMANTIC CLASSIFICATION OF UZBEK ANTHROPONYMIC PROVERBIAL PHRASEOLOGISMS - Mengboyev Otabek Alijon o‘g‘li (International Journal of Literature and Language Studies, 2026)
Abstract. This article investigates the semantic classification of Uzbek anthroponymic proverbial phraseologisms, that is, proverb-like fixed expressions, sayings, formulaic idioms, and paremiological units that contain a personal name or a name-like anthroponymic component. The study treats anthroponyms not as neutral lexical ornaments but as culturally loaded signs that condense social evaluation, collective memory, moral judgement, irony, typification, gender-role expectations, and pragmatic instruction. The article develops a semantic taxonomy based on the interaction between the proper-name component and the figurative meaning of the whole unit. The proposed classification includes: generic-personal anthroponyms, historical and legendary anthroponyms, religious and sacred anthroponyms, literary-folkloric anthroponyms, paired and rhyming names, kinship-marked name formulas, and pragmatic-ironic name formulas. Within these groups, Uzbek anthroponymic proverbial phraseologisms are interpreted according to the semantic domains of wisdom and folly, diligence and laziness, truth and deception, pride and modesty, social imitation, fate and patience, love and loyalty, public reputation, and communal moral order. The research relies on phraseological theory, paremiology, onomastics, and linguoculturology, and it argues that anthroponymic proverbial phraseologisms are a compact mechanism through which Uzbek folk consciousness transforms personal names into generalized cultural models.